PROSEDUR TENDER PENGADAAN KERETA API (Studi Kasus Pada PT. Industri Kereta Api (Persero) - Wanda Putri Oktaviani; Netty Lisdiantini; Agustinus Doedyk Setiyawan (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2022)
Tenders can mean auction or a system of buying and selling conducted by a party by inviting vendors (sellers or providers) to present the prices and quality needed. The best price and quality will be the winners. Auctions or tender systems are very popular, especially by companies, given the nominal amount and duration of contracts in an auction is very large and varied. This study aims to determine the tender procedures for procurement of railroad by PT KAI (Persero) from PT INKA (Persero), especially for post-qualification public tenders, as well as the documents required in the process. This study uses descriptive qualitative methods that are sourced from primary data, namely by conducting interviews, observations, and documentation of research objects and secondary data by conducting a study of relevant library materials. With the Triangulation Method the results of the research show that PT INKA (Persero) has carried out the tender procedure for the post-qualification of railroad procurement in accordance with applicable regulations and SOPs, even though the clarification stage is conducted simultaneously with the aanwinzjing stage; the stage of submitting, opening and evaluating documents is carried out at one time; and the refutation stage is not carried out if it has been determined as the winner of the tender.